Penyalahgunaan Scanlation Menurut Fatwa MUI No. 1/MUNAS VII/MUI/5/2005 Tentang Perlindungan Hak Kekayaan Intelektual - Yumna Luqyana Tanjung; Noor Azizah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Digitalization has had a significant impact on the comics industry in Indonesia, reaching new readers, expanding its role and potential in the creative economy. However, copyright piracy is a problem that is closely related to the development of information and communication technology. Scanlation is defined as the act of scanning and translation which refers to the distribution of comics by multiplying illegal digital comics for copying and distribution. This research is related to copyright law piracy which offers protection and law enforcement in dealing with scanlation fraud in Indonesia. The research method is an empirical juridical method regarding the enactment of Law No. 28 of 2014 regarding copyright and MUI fatwa NO. 1/MUNAS VII/MUI/5/2005. In the MUI fatwa NO. 1/MUNAS VII/MUI/5/2005 does not clearly regulate procedures for complaints of violations of Intellectual Property Rights (IPR) and the need for a concept of statutory regulations that regulate the form of protection of comic works in the digital space in order to create legal certainty for comic artists and their roles. active participation from law enforcement agencies, the public and the private sector to tackle acts of scanlation piracy